2017
DOI: 10.1007/s10950-017-9640-x
|View full text |Cite
|
Sign up to set email alerts
|

On the rotation of teleseismic seismograms based on the receiver function technique

Abstract: The receiver function (RF) technique is a well-established method to investigate the crustal and upper mantle structures based on three-component seismograms of teleseismic events. In the present study, we propose a modified automatic procedure to determine the back azimuth and polarization angles of a teleseismic event based on the RF technique. The method is tested for the recording of 3 permanent and 3 temporary broadband seismic stations located in the vicinity of Poland. Additionally, the analysis of Rayl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Figure 15 shows values of misorientations of all stations in the study area obtained with the use of three described methods; the permanent station GKP is outside the study area, but it is shown for comparison, as previous studies also reported its significant misorientation - Vecsey et al (2014) reported 41 • , Wilde-Piórko et al (2017) reported 39 and 45 • , and the result of this study is 34-37 • . For many stations, the results derived from the three methods are more or less consistent but with some conspicuous exceptions.…”
Section: Verification Of Sensors' Misorientationmentioning
confidence: 64%
See 1 more Smart Citation
“…Figure 15 shows values of misorientations of all stations in the study area obtained with the use of three described methods; the permanent station GKP is outside the study area, but it is shown for comparison, as previous studies also reported its significant misorientation - Vecsey et al (2014) reported 41 • , Wilde-Piórko et al (2017) reported 39 and 45 • , and the result of this study is 34-37 • . For many stations, the results derived from the three methods are more or less consistent but with some conspicuous exceptions.…”
Section: Verification Of Sensors' Misorientationmentioning
confidence: 64%
“…Black circles with crosses -orientation angles of permanent stations from direct, high-accuracy measurements in field by gyrocompass (Luděk Vecsey, Institute of Geophysics of Czech Academy of Sciences, personal communication, 2020). Black squares with crosses (for GKP station) -orientation angles reported by other studies (Vecsey et al, 2014;Wilde-Piórko et al, 2017). The AniMaLS project is an experimental seismic study of the physical properties and geological structure of the lithosphere and sublithospheric mantle beneath the Polish Sudetes (NE margin of the Variscan orogen), with a complex history of tectonic evolution.…”
Section: Verification Of Sensors' Misorientationmentioning
confidence: 99%
“…It is characterized by a thick three‐layer crust with an additional fast lower crustal layer (Grad et al., 2003). The East European Craton is of Precambrian origin and overlain by a young thin sedimentary cover (Bogdanova et al., 2006) which leads to strong reverberations in the P‐receiver function for SUW (Wilde‐Piórko et al., 2017)…”
Section: Data Setsmentioning
confidence: 99%
“…Some examples include earthquake source investigations, anisotropy studies, receiver function analyses or body‐ and surface‐wave polarization studies (e.g., Ekström and Busby ; Wilde‐Piórko et al . , Lim et al . ).…”
Section: Horizontal Orientations Of the Borehole Sensorsmentioning
confidence: 99%
“…Misorientation of seismometers with respect to the geographic coordinate system is a very important variable for threecomponent seismological analyses that require the rotation of the seismic records from the original geographic coordinates ZNE (vertical, north-south, east-west) into the ZRT (vertical, radial, transverse) or into the ray-oriented LQT (Pwave direction, SV-wave direction, SH-wave direction) coordinate systems. Some examples include earthquake source investigations, anisotropy studies, receiver function analyses or body-and surface-wave polarization studies (e.g., Ekström and Busby 2008;Wilde-Piórko et al 2017, Lim et al 2018). The orientation is usually determined by indirect methods after the installation of the seismometer, and the azimuths of the horizontal components are reported as auxiliary data (e.g., Ekström and Busby 2008).…”
Section: H O R I Z O N T a L O R I E N T A T I O N S O F T H E B O R mentioning
confidence: 99%